Dynamics of Coastal Land Use Change and Prospects for Sustainable Marine Ecotourism in Nusa Penida Island - Prihadi, Donny Juliandri; Junirahma, Nur Sakinah; Dhahiyat, Ahmad Prawira; Pamungkas, Wahyuniar; Krisnadi, Fanny; Ainni, Chusnul Firaqie (Formosa Journal of Multidisciplinary Research, 2024)
Nusa Penida has rich marine ecosystems, such as coral reefs and mangroves, which are residents' main source of income through fisheries, seaweed cultivation, and tourism. Land use change in Jungut Batu Village, Nusa Lembongan, has implications for the environment and economy in the coastal area of Nusa Penida. This study uses secondary data and Google Earth software to analyze changes in the area. From 2009 to 2020, significant changes occurred from seaweed cultivation to tourism land and back to seaweed cultivation during the pandemic. This analysis reflects the evolving economic dynamics and environmental impacts. The transformation from cultivated land to a marine ecotourism destination demonstrates an evolution in approaches to sustainable land use. However, the negative impacts of mass tourism highlight the need for a shift towards environmentally friendly and sustainable tourism. Collaboration between communities, tourism actors, government, and continued research is key in developing an effective and sustainable ecotourism model for Nusa Penida.